Sistem Pakar Untuk Mendiagnosa Gangguan Kesehatan Mental Menggunakan Algoritma Genetika - Daniel Dwi Kurnia (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
Abstract Healthy or not a person's life is not only based on physical but mental. Mental and physical health must be balanced to have a good life. Many people do not pay attention to their mental health and those around them so that their lives can no longer be saved. One of the consequences of disturbed mental health is cases of depression, self-harm (cutting) to suicide. Mental Health Disorders (Mental Health Disorders) include Schizophrenia, Depression, Post Traumatic Stress Disorder (PTSD), Bipolar, Paranoid and so on. Based on the existing problems, the author finally designed a website-based expert system application. An expert system for this is made using the PHP programming language and MySQL database using genetic algorithms. Genetic algorithm is a method that can provide solutions in solving heuristic problems and is widely used to solve optimization problems. The genetic algorithm used is Certainty Factor. The results of system testing that have been carried out on 20 experimental cases stated that 85% were in accordance with the results expected by expert data.